Clothing Examination in Forensic Medicine - Can, Muhammet; Üner, Hüseyin Bülent; Sarıkaya, Özlem; Tok, Mehmet; Berber, Gürol; Akgül, Esin; Çerkezoğlu, Ali (The Bulletin of Legal Medicine, 2005)
Physical evidences have significant role in understanding and determining the manner of the forensic event. Chemical and physical examination of the clothing of the deceased and/or the injured, with wounding inflicted by firearms and various instruments (incising, stabbing etc.), is important with regard to the forensic and medical consequences. This study deals with clothing examinations performed at Council of Forensic Medicine-Department of Physical Examination, between 1995 and 1999. The relevant reports have been evaluated as to the impediments during the course of obtaining and delivery of the clothes and focuses on the factors that might affect the results of clothing examination. Of the 1172 files sent for forensic evaluation; range of fire, clothing examination, type of weapon were main questions by 61%, 18% and 4% respectively. There were errors in obtaining, preservation and handling the clothes. In some cases, the clothes were sent without files and autopsy report. Thus, it is concluded that the procedures for clothing examination should be applied in all phases.Key words: Forensic medicine, clothing examination, firing distance determination, gunshot residues, gun types.
Keywords: forensic medicine; clothing examination; firing distance determination; gunshot residues; gun types